Direct observation of double valence-band extrema and anisotropic effective masses of the thermoelectric material SnSe. (8th December 2017) - Nagayama, Takanobu; Terashima, Kensei; Wakita, Takanori; Fujiwara, Hirokazu; Fukura, Tetsushi; Yano, Yuko; Ono, Kanta; Kumigashira, Hiroshi; Ogiso, Osamu; Yamashita, Aichi; Takano, Yoshihiko; Mori, Hitoshi; et al.
Abstract: Synchrotron-based angle-resolved photoemission spectroscopy is used to determine the electronic structure of layered SnSe, which was recently turned out to be a potential thermoelectric material. We observe that the top of the valence band consists of two nearly independent hole bands, whose tops differ by ∼20 meV in energy, indicating the necessity of a multivalley model to describe the thermoelectric properties. The estimated effective masses are anisotropic, with in-plane values of 0.16–0.39 m 0 and an out-of-plane value of 0.71 m 0, where m 0 is the rest electron mass. Information of the electronic structure is essential to further enhance the thermoelectric performance of hole-doped SnSe.